Mood profiles of amateur triathletes: Implications for mental health and performance - Parsons-Smith, Renée L.; Barkase, Sherry; Lovell, Geoff P.; Vleck, Veronica; Terry, Peter C. (Frontiers in Psychology, 2022)
Moods have been shown to be predictive of athletic performance and a reflection of mental health status. The aims of our study were (a) to compare pre-race mood scores of triathletes with population norms; (b) to compare pre-race mood scores of triathletes grouped by gender and age bands; (c) to explore whether six distinct mood profile clusters reported in the literature were evident among triathletes and their respective prevalence; (d) to determine if pre-race mood scores predicted triathlon performance; and (e) to interpret our findings in terms of the risk of mental health issues for triathletes. Participants were 592 age-group triathletes (also referred to as recreational or amateur triathletes) who completed the Brunel Mood Scale pre-race and recorded their time goal for the race. Mean mood scores deviated significantly from population norms, with Tension and Vigor scores at the 55th and 54th percentile, respectively, and Depression, Anger, Fatigue, and Confusion scores between the 42nd and 46th percentile. Females reported higher Tension scores than males (p < 0.001), and those in the 18–25 years and 26–35 years age bands reported higher Tension scores than those in the 46–55 years age band (p < 0.008). Using k-means cluster analysis, six distinct mood profiles were identified, the distribution of which approximated the general population, except for a low prevalence of very negative profiles. Mean scores for Depression and Anger were exceptionally low and only 1.5% of triathletes, compared to the normal prevalence of 5%, reported an “inverse Everest” profile, which is associated with elevated risk of psychopathology. Mood scores did not predict triathlon performance, assessed by finish time as a percentage of time goal. Results showed an association between triathlon participation and psychological well-being. Findings will inform future investigations of mood responses among triathletes and provide a relevant point of reference for applied practitioners who work with triathletes.